Gillnet selectivity and size and age structure of an alpine Arctic char ( Salvelinus alpinus) population - Finstad, Anders G; Jansen, Peder A; Langeland, Arnfinn (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
The aim of the present study was to address possible implications of biased sampling for the commonly adopted uni- and bi-modal size structures and unimodal age structures in Arctic char (Salvelinus alpinus) populations. Multimesh gill nets were used to sample an allopatric population of Arctic char in an alpine lake in central Norway. Direct estimates of gillnet selectivity for different length-classes of Arctic char were obtained by mark-recapture experiments and by successive removal methods. The observed size and age structure in gillnet samples was significantly different from the estimated size and age structure of the Arctic char population when catches were corrected for gillnet selectivity. An observed unimodal size and age structure was a direct result of gillnet selectivity, as smaller and younger fish were underrepresented in gillnet catches. Moreover, an abrupt increase in gillnet selectivity for large Arctic char was related to a niche shift to cannibalism. A model that explains bimodal size distributions in gillnet catches as a result of ontogenetic behavioural change is presented. Complex ontogenetic growth and mortality patterns that have been suggested to be essential in structuring modal Arctic char populations were superfluous in explaining the observed modal population structure in the present study.